Answer:
C and D
Step-by-step explanation:
The quadratic formula is
x= (-b±√b²-4ac)/2a
The formula uses the numerical coefficients in the quadratic equation.
The general quadratic equation is ax²+bx+c where a, b and c are the numerical coefficients
So, lets try and see;
A.
![5x+4=3x^4-2\\\\=3x^4-5x-2-4\\=3x^4-5x-6\\a=3,b=-5,c=-6](https://tex.z-dn.net/?f=5x%2B4%3D3x%5E4-2%5C%5C%5C%5C%3D3x%5E4-5x-2-4%5C%5C%3D3x%5E4-5x-6%5C%5Ca%3D3%2Cb%3D-5%2Cc%3D-6)
But due to the fact that in this equation you have x⁴, the equation is not a quadratic equation thus can not be solved using this formula
B
![-x^2+4x+7=-x^2-9\\\\\\=-x^2+x^2+4x+7+9\\=4x+16](https://tex.z-dn.net/?f=-x%5E2%2B4x%2B7%3D-x%5E2-9%5C%5C%5C%5C%5C%5C%3D-x%5E2%2Bx%5E2%2B4x%2B7%2B9%5C%5C%3D4x%2B16)
C
![9x+3x^2=14+x-1\\\\\\=3x^2+9x-x-14+1\\\\=3x^2+8x-13\\\\\\a=3,b=8,c=-13\\](https://tex.z-dn.net/?f=9x%2B3x%5E2%3D14%2Bx-1%5C%5C%5C%5C%5C%5C%3D3x%5E2%2B9x-x-14%2B1%5C%5C%5C%5C%3D3x%5E2%2B8x-13%5C%5C%5C%5C%5C%5Ca%3D3%2Cb%3D8%2Cc%3D-13%5C%5C)
D.
![2x^2+x^2+x=30\\\\\\=3x^2+x-30\\\\\\a=3,b=1,c=-30](https://tex.z-dn.net/?f=2x%5E2%2Bx%5E2%2Bx%3D30%5C%5C%5C%5C%5C%5C%3D3x%5E2%2Bx-30%5C%5C%5C%5C%5C%5Ca%3D3%2Cb%3D1%2Cc%3D-30)
From the checking above, the equations will be C and D
Answer:
ok so the two other ways are- 6:2 and 9:3
And the second part- 5
Step-by-step explanation:
Answer:
The first one is -2x^2 - 21x + 4, the second one is -15 (I think, not 100% sure), the third one is 4xyz + 3yz + 5x - 4 (also not 100% on this one)
Answer:
You’re right!
Step-by-step explanation:
It IS 3, heres why:
it follows the same rule each time:
2X=Y
1 times 2 is 2
6 times 2 is 12
11 times 2 is 22
16 times 2 is 36
thats proportionate! :D
i hope this helps!
Answer: A,D
Step-by-step explanation: I think that it is right?